(untitled) (FULafia Journal of Science and Technology, 2018)
The effects of ethanolic stem bark extracts of Syzigium guineense on trophozoites of Entamoeba histolytica in the liver of swiss mice was studied in an acute toxicological trial. Amoebiasis was induced by injection of E.histolytica trophozoites into the caecum and monitored for 7 days after inoculation. Successfully infected mice were divided into 5 groups and treated for 7 days. Group 1 was treated with 2mg/kg/day normal saline (negative control), groups 2, 3, 4 were treated with oral doses of S. guineense of 1000, 500 and 250 mg/kg/day respectively. Group 5 was treated with an oral dose of metronidazole (positive control) 15mg/kg/day. Mice were sacrificed on the 8th day and dissected to remove the liver for histological preparation and examination. Weight measurement revealed significant reduction (p<0.05) in all groups while the median lethal dose (LD50) of the extract was obtained to be 2828.43mg/kg. Histological investigations showed inflammation of hepatocyte cells and early signs of necrosis